PROCESSES OF OXYGEN DESOPRPTION IN HIGH-DENSITY LANTHANUM-STRONTIUM MANGANITE La0.6Sr0.4MnO3-d - L. I. Gurskii; N. A. Kalanda; A. N. Chobot; Yu. V. Sukhodolov; G. M. Chobot; P. N. Kireev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Characteristic properties of the formation of physical - chemical properties of a manganite with the composition La0.6Sr0.4MnO3-d were considered. It was determined that two titration current minima depending on the heating rate and the partial pressure of oxygen (pO2) exist at different temperatures, heating rates and partial pressures of oxygen. It is supposed that extreme values of the titration current are caused by breaking of bands of anions existing in two different forms with the tetravalent manganese, as well as by the excessive superstoichiometric oxygen which partially compensate the presence of Mn4+ cations, and by oxygen recovering the electroneutrality of the system appearing due to a decrease of the charge value due to the introduction of Sr2+. It was established that the activation energy of oxygen diffusion is decreasing and reached the minimal value 241 kJ/mole at pO2=5 Pa, with a subsequent increase up to ~273 kJ/mole at pO2= 150 Pa and d=0,004, with the increase of oxygen defects concentration in the La0.6Sr0.4MnO3-d anion sublattice. Concentration dependence of the activation energy of oxygen diffusion is motivated by a formation of the stressed layer, placed near the surface of grains which are depleted with oxygen and at the same time they are a buffer for the oxygen diffusion.